A Pragmatic Analysis of Questions and Responses in American Defense Attorneys' Cross-examinations: رحاب عبد الجليل سعيد العطار (Journal of the College of Education for Women, 2021)
The structure of the interrogation process in cross-examinations is said to be diverse and complex in terms of question-response typology. This is because the counsel has to extract truth from an opposing party’s witness whose views are expected to advocate that party's views regarding the case. Accordingly, the study which is basically quantitative in nature aims to investigate what the examining party intends to obtain out of these questions and which of these questions are the most prevalently used. It also aims to measure the amount of cooperativity in witnesses' responses. Accordingly, three transcripts of cross-examination have been analyzed, using a pragmatically-oriented approach. The approach draws on Stenstorm (1984) and Archer's (2005) classification of questions; Stenstorm (1984) and Archer's (2002) classificatory scheme of responses which is based on the strategies of violating Grice's (1975) maxims to determine the degree of cooperation on the part of respondents. The analysis revealed a diversity in the attorneys' method, making the use of four types of leading questions as well as non-leading ones represented by WH questions. The latter recorded the least percentage in comparison with the overall percentage of leading questions. That is; a preference is shed on the part of cross-examining counsel towards leading over non-leading questions. Moreover, the majority of the responses given have indicated the witnesses' commitment to the purpose and format of the questions posed, showing a high level of cooperativity on the part of those witnesses